DETERMINATION AND ANALYSIS OF MACRO-ELEMENTS, VITAMINS, AND FLAVONOIDS IN THE LEAVES OF PAULOWNIA AND ROSMARINUS PLANTS - Ibragim Askarov Rakhmanovich; Tursunoy Usmanova Erkinovna (Modern American Journals, 2025)
This scientific study focuses on the determination and comprehensive analysis of macroelements, water-soluble vitamins, and flavonoid in the leaves of Paulownia and Rosmarinus officinalis (commonly known as rosemary), two plant species introduced and cultivated in the Fergana region of Uzbekistan. The main objective of this research is to examine the chemical composition of these plants using advanced analytical techniques and to assess their potential applications in pharmaceutical, nutraceutical, and food industries as sources of biologically active compounds.
Keywords: Macro-elements, inductively coupled plasma optical emission spectroscopy (ICP-OES), vitamins, thiamine (B1), riboflavin (B2), pyridoxine (B6), folic acid (B9), nicotinic acid (PP) B3, ascorbic acid (C).